Brief Report: High Sensitivity and Specificity of the Cepheid Xpert HIV-1 Qualitative Point-of-Care Test Among Newborns in Botswana. (15th August 2017) - Ibrahim, Maryanne; Moyo, Sikhulile; Mohammed, Terence; Mupfumi, Lucy; Gaseitsiwe, Simani; Maswabi, Kenneth; Ajibola, Gbolahan; Gelman, Rebecca; Batlang, Oganne; Sakoi, Maureen; Auletta-Young, Chloe; Makhema, Joseph; et al.
Abstract : Background: HIV point-of-care (POC) testing allows for early infant HIV diagnosis and treatment, but POC accuracy at birth and in the setting of antiretroviral prophylaxis for the prevention of mother-to-child HIV transmission is unknown. Methods: We evaluated the Cepheid Xpert HIV-1 Qual POC test against the Roche Taqman HIV-1 DNA polymerase chain reaction (PCR) platform using dried blood spots from 15 HIV-infected and 75 HIV-exposed uninfected newborns. These infants were screened for HIV at <96 hours of life at 5 hospital maternity wards in Botswana; all infants received postexposure antiretroviral prophylaxis with single-dose nevirapine and zidovudine, and most mothers received 3-drug antiretroviral therapy in pregnancy and at delivery. Results: Fourteen of the 15 PCR positive samples tested positive by Cepheid POC, yielding a sensitivity of 93.3% (95% confidence interval: 68.1 to 99.8). Baseline viral load among positive infants ranged from <40 to >10, 000, 000 copies/mL, with a median of 2403 copies/mL. The HIV RNA for the infant with false-negative POC testing was 1661 copies/mL. Of note, 2 infants with low HIV RNA (<40 and 272 copies/mL) were correctly identified as HIV positive by Cepheid POC. All the 75 PCR-negative samples tested negative by Cepheid POC, yielding a specificity of 100% (95% confidence interval: 96.1 to 100). Discussion: Our study demonstrates high sensitivity and specificity for the Cepheid POC assay in the first week of life despite early infection and antiretroviral prophylaxis. This platform may be a useful approach for adding early infant HIV diagnosis to current testing programs.